Pemanfaatan Multimedia Pembelajaran Interaktif bagi Guru PAUD - Siswanti, Dian Novita; Daud, Muh. (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The aim of this research is to find out an overview of the use of interactive multimedia learning for PAUD teachers. This research uses the library research method or literature review. Data was obtained through 9 scientific articles related to the use of multimedia, interactive learning, PAUD teachers. Data was analyzed using content analysis. The research results show that the use of interactive multimedia in learning can also increase understanding, positive emotions and behavior of PAUD children during the learning process. In conclusion, multimedia can be useful in increasing interaction between teachers and students in PAUD in the learning process. The implication of this research is to provide an understanding of the importance of improving teacher competence, especially in preparing interesting, innovative, efficient and effective learning media in accordance with the growth and development of early childhood in PAUD.